Odpowiedź :
Odpowiedź:
a)
[tex]\frac{x}{3} + 1 = \frac{5}{6} + \frac{x}{2}[/tex]
[tex]2x + 6 = 5 + 3x[/tex]
[tex]2x - 3x = 5 - 6[/tex]
[tex]-x = - 1[/tex]
[tex]x = 1[/tex]
b)
[tex]\frac{2x-3}{4} = \frac{1}{2} + x[/tex]
[tex]2x - 3 = 2 + 4x[/tex]
[tex]2x - 4x = 2 + 3[/tex]
[tex]-2x = 5[/tex]
[tex]x = -\frac{5}{2}[/tex]
c)
[tex]\frac{x + 2}{9} + \frac{x - 1}{3} = 1[/tex]
[tex]x + 2 + 3(x - 1) = 9[/tex]
[tex]x + 2 + 3x - 3 = 9[/tex]
[tex]4x - 1 = 9[/tex]
[tex]4x = 9 + 1[/tex]
[tex]4x = 10[/tex]
[tex]x = \frac{5}{2}[/tex]
d)
[tex]\frac{2x + 3}{5} = \frac{2 - x}{3} + x[/tex]
[tex]3(x + 3) = 5(x-2) + 15x[/tex]
[tex]6x + 9 = 10 - 5x + 15x[/tex]
[tex]6x + 9 = 10 + 10x[/tex]
[tex]6x - 10x = 10 - 9[/tex]
[tex]-4x = 1[/tex]
[tex]x = - \frac{1}{4}[/tex]
e)
[tex]\frac{3x - 5}{2} - \frac{5x - 1}{10} = 0[/tex]
[tex]5(3x-5)-(5x-1)=0[/tex]
[tex]15x - 25 - 5x + 1 = 0[/tex]
[tex]10x - 24 = 0[/tex]
[tex]10x = 24[/tex]
[tex]x = \frac{12}{5}[/tex]
f)
[tex]\frac{x}{2} = \frac{2}{5} * (4-x)-4[/tex]
[tex]\frac{x}{2} = \frac{8}{5} - \frac{2}{5} x - 4[/tex]
[tex]\frac{x}{2} = - \frac{12}{5} - \frac{2}{5} x[/tex]
[tex]5x = -24 - 4x[/tex]
[tex]5x + 4x = - 24[/tex]
[tex]9x = -24[/tex]
[tex]x = - \frac{8}{3}[/tex]
g)
[tex]\frac{2x - 1}{5} - \frac{x - 2}{2} = 0,7x[/tex]
[tex]\frac{2x-1}{5} - \frac{x-2}{2} = \frac{7}{10}x[/tex]
[tex]2(2x-1)-5(x-2)=7x[/tex]
[tex]4x - 2 - 5x + 10 = 7x[/tex]
[tex]-x + 8 = 7x[/tex]
[tex]-x - 7x = -8[/tex]
[tex]-8x = -8[/tex]
[tex]x = 1[/tex]
h)
[tex]2x - \frac{3x + 5}{4} = -\frac{1}{4} x - 1[/tex]
[tex]8x - (3x+5)=-x-4[/tex]
[tex]8x-3x-5=-x-4[/tex]
[tex]5x - 5 = - x - 4[/tex]
[tex]5x + x = -4 + 5[/tex]
[tex]6x = 1[/tex]
[tex]x = \frac{1}{6}[/tex]